The Effect of Age-At-Release on Survival of Adoptive Parent-Reared Bobwhite Chicks - Kyle D. Lunsford; Theron M. Terhune II; James A. Martin (National Quail Symposium Proceedings, 2017)
Translocation of wild northern bobwhites (Colinus virginianus) to restore local populations is a viable conservation tool under some scenarios; however, the supply of wild bobwhites is limited. Bobwhites can be artificially propagated, as an alternative to translocation, using methods that mimic natural brood-rearing. The parent-rearing adoptive process (PRAP) uses wild-strain bobwhite adults to brood and foster newly hatched wild-strain chicks in outdoor aviaries that emulate a natural environment. Adoptive parent-reared bobwhites have higher survival rates than artificially-reared bobwhites but only a single age-of-release (i.e., 6-weeks) has been tested. We tested the effect of age-at-release (3, 6, and 9-weeks) on adoptive parent-reared chicks released on the same date in Hanna Hammock of Tall Timbers Research Station. All chicks were marked with patagial wing tags and a subset of the group received radio transmitters. The 3-week-olds (n = 25) received suture-style transmitters and 6-week-olds (n = 30) and 9-week-olds (n = 30) received necklace-style transmitters. Our adoptive parent-reared chicks had low survival rates over 3 months post-release, the 9-week age group had the highest overall survival rates which could portend that increased physiological development may aid in increasing the survivability of adoptive parent-reared bobwhites. The low survival rates across all 3 age classes calls into question the efficacy of the PRAP as a bobwhite restoration method. Our results do suggest that additional modifications to release age (> 9-weeks) should be explored along with further modifications to the PRAP. Additional modifications include incorporating predator avoidance training, altering release dates, and changing nutritional regimes. These results should caution the bobwhite community to remain suspect when deriving conclusions about the PRAP until all process modifications have been fully evaluated by scientific research.
Keywords: artificial propagation; age effects; chicks; Colinus virginianus; northern bobwhite; parent-reared; Red Hills; reintroduction; restoration; Tall Timbers Research Station